1845 Conn. Acts 10, An Act Prohibiting the Firing of Guns and Other Fire Arms in the City of New Haven, chap. 10 - (:unkn) unknown (General Publisher, 1845)
Prohibited the discharge of any gun or other firearm of any knd within the city limits of New Haven. Violators fined seven dollars, or by imprisonment not exceeding thirty days.
--
Keywords: DISCHARGE